Radiation dose reference card for interventional radiology procedures: Experience in a tertiary referral centre - Varghese, Anna; Keshava, Shyamkumar N; Moses, Vinu; Koshy, George; Mammen, Suraj; Ahmed, Munawwar; Livingstone, Roshan S (Indian Journal of Radiology and Imaging, 2019)
Background: Fluoroscopy-guided interventions can potentially increase radiation risk to patients, if awareness on angiographic imaging technique and radiation dose is neglected. Aim: To develop patient radiation dose reference card from standardized imaging techniques for various radiology interventions performed using flat detector based angiography system. Materials and Methods: Real-time monitoring of angiographic exposure parameters and radiation dose were performed for 16 types of radiological interventions. Effective dose (ED) was estimated from dose area product (DAP) using PCXMC Monte Carlo simulation software. Radiation risk levels were estimated based on Biological Effects of Ionising radiation (BEIR) report VII predictive models for an Asian population. Results: Pulse rates of 7.5 pps and 0.6 mm Copper filtration during fluoroscopy and 4 frames per second (fps) and 0.1-0.3 mm Cu filtration during image acquisitions were found to reduce radiation dose. Owing to increased number of image acquisitions, DAP was highest during diagnostic spinal angiography 186.7 Gycm2 (44.0–377.5). This resulted in highest ED of 59.4 mSv with moderate risk levels (1 in 1000 to 1 in 500). Most of the radiological interventions had low radiation risk levels (1 in 10,000 to 1 in 1000). Conclusion: The patient radiation dose reference card is valuable to the medical community and can aid in patient counselling on radiation induced risk from radiological interventions.
Keywords: Flat detector; interventional radiology; radiation dose reference card